PENGEMBANGAN MODUL PELUANG UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA - Ndruru, Destimulia (FAGURU: Jurnal Ilmiah Mahasiswa Keguruan, 2022)
The type of research used is research development or Research and Development (R&D) with a 4D model (Define, Design, Development, Disseminate). Based on the results of research and discussion, the opportunity module has met the criteria of being valid, practical and effective. The results of the validity with an average of 91.66% and categorized as very valid. The average practicality result in the limited class trial is 4.11 with a percentage of 82.2% and is categorized as very practical, then the average practicality result in the field trial is 4.16 with a percentage of 83.26% and is categorized as very practical. The results of the effectiveness of the limited class trial obtained an average of 0.45 in the medium category, and the field class trial obtained an average of 0.72 in the high category. The developed module can be used to improve students' mathematics learning outcomes on probability material.